Reinforcing Public Compliance Through Strategic Communication: Implementation of the Electronic Traffic Law Enforcement (ETLE) Program in Parepare City - Nurdiansyah, Iskandar; Harahap, Hamida Syari (Palakka : Media and Islamic Communication, 2025)
This study analyzes the strategic communication approach in the implementation of the Electronic Traffic Law Enforcement (ETLE) program in Parepare City. ETLE was introduced as a digital-based traffic law enforcement system to increase transparency, efficiency, and community discipline through automated surveillance and ticketing. The effectiveness of ETLE, however, is highly influenced by how the program is communicated to the public. Using a qualitative descriptive design, data were obtained through interviews with traffic officers and community members, non-participant observation, and documentation analysis. The findings reveal that the Parepare Traffic Police employ a multi-channel communication model that integrates interpersonal communication, digital media campaigns, and stakeholder-based socialization. This strategy positively affects public understanding and compliance, although several challenges persist, including misconceptions about ETLE, limited digital literacy among certain age groups, and inconsistent dissemination of information. The study concludes that ETLE success requires not only technological readiness but also a strategic, targeted, and participatory communication approach. Strengthening collaboration between law enforcement institutions, local government, media, and community leaders is recommended to optimize law compliance and improve acceptance of digital policing.